The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10620-010-1305-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Index for Predicting Significant Liver Fibrosis: Comparison of Diagnostic Performances in Patients with Chronic Hepatitis B and C

Abstract: Background/Aims The majority of non-invasive markers of liver fibrosis have been developed in patients with chronic hepatitis C. We aimed to develop a formula for predicting significant fibrosis in patients with chronic viral hepatitis and to compare the usefulness of published models derived from the data obtained from patients with chronic hepatitis C. Methods Serum markers and the METAVIR stage of fibrosis in liver biopsy specimens were compared prospectively in patients with chronic hepatitis B and C (esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Sixty‐eight full‐text articles were eligible for evaluation and 29 studies were excluded for the similar studies from one center (n = 8), failure to use biopsy (n = 5), data incomplete (n = 8), or small sample size (n = 8). Finally, 39 studies were selected for evaluation and meta‐analysis . All studies included in this review were from Europe and Asia (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty‐eight full‐text articles were eligible for evaluation and 29 studies were excluded for the similar studies from one center (n = 8), failure to use biopsy (n = 5), data incomplete (n = 8), or small sample size (n = 8). Finally, 39 studies were selected for evaluation and meta‐analysis . All studies included in this review were from Europe and Asia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐six studies used the Metavir score, six used the Ishak score, five used the Scheuer score, and one used the Batts and Ludwig score. Thirty‐three studies included HBV‐monoinfected patients (n = 8,789); three studies included HBV‐infected patients with other factors, including alcohol consumption (n = 512); and one study included patients with HCC (n = 76) . According to the QUADAS score, the methodological quality of the included studies was satisfactory (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously estimated the aspartate aminotransferase platelet ratio index (APRI), calculated as the AST [ULN]/platelet count [10 3 /mL] ×100, from a database (37). Unfortunately, our results did not show the APRI to be a predictor of DM, as most of our patients had either no or mild liver fibrosis.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have demonstrated that non-invasive serum markers can be used to predict the onset of DM (35)(36)(37). We previously estimated the aspartate aminotransferase platelet ratio index (APRI), calculated as the AST [ULN]/platelet count [10 3 /mL] ×100, from a database (37).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs and TIMPs play an important role in hepatic fibrosis. [1][2][3] In particular, serum MMP-2 concentration has been reported to correlate with the degree of periportal necrosis and fibrosis presented and the total histological activity score [4][5][6] while serum TIMP-1 has been reported to correlate with liver fibrosis in a cohort of HIV-HCV co-infected patients, 6,7 in HCV infection, [8][9][10] in alcoholic liver disease, 11 in HBV infection 12 and in parasitic infestation. 13 What all these studies would seem to indicate is that whatever might be the cause of liver damage, the mechanism of fibrogenesis would appear to be the same.…”
Section: Introductionmentioning
confidence: 99%